Perlindungan hukum terhadap harta benda wakaf sebagai aset publik di kecamatan Wiradesa kabupaten Pekalongan - Achmad Irwan Hamzani; Mukhidin Mukhidin (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2016)
The treasure of the waqf is a public asset that should be protected by law. Waqf is a legal act that itsimplementation must be in accordance with statutory procedures. Mandatory legal act waqf deed pledgespoured in endowments. But in practice there is still a committed implementation of the waqf notaccording to legal procedures. Implementation of the waqf is not stated in the Deed of Pledge Waqf ashappened in the district Wiradesa Pekalongan thus has no legal force. Departing from this fact researchis needed to describe the implementation of endowments in the District Wiradesa and formulate legalsafeguards against waqf property as a public asset in the District Wiradesa. This research is a fieldresearch. The approach is sociological, thus falling within the scope of empirical legal research. Thecollection of data through observation and interviews. Data were analyzed using the model of induction-interpretation. The results showed that the waqf property in District Wiradesa many do not haveauthentic proof recognized by the law. Necessary legal means to protect the property of the waqf ofpotential irregularities.